A prospective study for treatment of nasal valve collapse due to lateral wall insufficiency: Outcomes using a bioabsorbable implant. (14th May 2018) - Stolovitzky, Pablo; Sidle, Douglas M.; Ow, Randall A.; Nachlas, Nathan E.; Most, Sam P.
Abstract : Objective: To examine 6‐month outcomes for treatment of lateral nasal wall insufficiency with a bioabsorbable implant. Study Design: Prospective, multicenter, nonrandomized, single‐blinded study. Methods: One hundred and one patients with severe‐to‐extreme class of Nasal Obstruction Symptom Evaluation (NOSE) scores were enrolled at 14 U.S. clinics (September 2016–March 2017). Patients were treated with a bioabsorbable implant designed to support lateral wall, with or without concurrent septoplasty and/or turbinate reduction procedure(s). NOSE scores and visual analog scale (VAS) were measured at baseline and month 1, 3, and 6 postoperatively. The Lateral Wall Insufficiency (LWI) score was determined by independent physicians observing the lateral wall motion video. Results: Forty‐three patients were treated with implant alone, whereas 58 had adjunctive procedures. Seventeen patients reported 19 adverse events, all of which resolved with no clinical sequelae. Patients showed significant reduction in NOSE scores at 1, 3, and 6 months postoperatively (79.5 ± 13.5 preoperatively, 34.6 ± 25.0 at 1 month, 32.0 ± 28.4 at 3 months, and 30.6 ± 25.8 at 6 months postoperatively; P  < 0.01 for all). They also showed significant reduction in VAS scores postoperatively (71.9 ± 18.8 preoperatively, 32.7 ± 27.1 at 1 month, 30.1 ± 28.3 at 3 months, and 30.7 ± 29.6 at 6 months postoperatively; P  < 0.01 for all). These results were similar in patients treated with the implant alone compared to those treated with the implant and adjunctive procedures. Consistent with patient‐reported outcomes, postoperative LWI scores were demonstrably lower (1.83 ± 0.10 and 1.30 ± 0.11 pre‐ and postoperatively; P  < 0.01). Conclusion: Stabilization of the lateral nasal wall with a bioabsorbable implant improves patients' nasal obstructive symptoms over 6 months. Level of Evidence: 2b. Laryngoscope, 2483–2489, 2018